PENYELESAIAN WANPRESTASI ATAS PERJANJIAN KREDIT DI PT BANK BRI UNIT MUARO DENGAN NASABAH DI PENGADILAN NEGERI MUARO KELAS II (Studi Putusan Nomor 3/Pdt.G.S/2019/PN Mrj) - Muzni Karmila, Dwikornida dan (Normative Jurnal Ilmiah Hukum, 2023)
National development is a sustainable development effort in the context of creating a just andprosperous society based on Pancasila and the 1945 Constitution of the Republic of Indonesia.Loan agreements have been regulated and determined in Chapter Thirteen of the Third Book ofthe Civil Code, in Article 1754 of the Civil Code which clearly states that, "A loan agreement isan agreement whereby one party gives to another party a certain amount of goods that are usedup due to usage, with the condition that the latter party will return the same amount of the sametype and condition". Decision Number 3/Pdt.G.S/2019/PN Mrj is that a debtor does not fulfillobligations to a creditor. The formulation of the problem is what is the consideration of theMuaro District Court Judge regarding the default case between PT Bank BRI Unit Muaro and acustomer in Sijunjung Regency and what are the legal consequences of the judge's decision inresolving default cases between Bank BRI Unit Muaro and a customer at the Class II MuaroDistrict Court.